Metformin alleviates allergic airway inflammation and increases Treg cells in obese asthma. Issue 4 (9th January 2021) - Guo, Yimin; Shi, Jianting; Wang, Qiujie; Hong, Luna; Chen, Ming; Liu, Shanying; Yuan, Xiaoqing; Jiang, Shanping
Abstract: Obesity increases the morbidity and severity of asthma, with poor sensitivity to corticosteroid treatment. Metformin has potential effects on improving asthma airway inflammation. Regulatory T cells (Tregs) play a key role in suppressing the immunoreaction to allergens. We built an obese asthmatic mouse model by administering a high‐fat diet (HFD) and ovalbumin (OVA) sensitization, with daily metformin treatment. We measured the body weight and airway inflammatory status by histological analysis, qRT‐PCR, and ELISA. The percentage of Tregs was measured by flow cytometry. Obese asthmatic mice displayed more severe airway inflammation and more significant changes in inflammatory cytokines. Metformin reversed the obese situation and alleviated the airway inflammation and remodelling with increased Tregs and related transcript factors. The anti‐inflammatory function of metformin may be mediated by increasing Tregs.